Оцінка рівня економічної безпеки лісогосподарських підприємств зони Українського Полісся - Cherchyk, Larysa; Shubalyi, Alexander; Khumarova, Nina; Cherchyk, Artur (Dr. Viktor Koval, 2020)
Introduction. Under such conditions, the problem of assessing the economic security of enterprises is actualized, which is designed to identify threats that arise in the competitive environment and the internal environment of the enterprise, to identify strengths and weaknesses in the activities of the enterprise, on the basis of which management decisions are made at the strategic level, to prevent negative situations at the operational levels of enterprise management. Aim and tasks. The purpose of the study is to assessing the economic security of forest enterprises in the Ukrainian Polissya region. Objectives of the study: generalization of scientific approaches to assessing the economic security of enterprises; determination of criteria for assessing the economic security of forestry; development and testing of methods for assessing the economic security of forestry in the Ukrainian Polissya region. Results. The calculations show a high and sufficient level of economic security in the studied forestry enterprises. However, there is a decrease in financial security indicators, which requires the adoption of current and strategic management decisions to improve financial results and improve the financial condition of forestry enterprises. The main problem is the inefficient structure of exports, namely the predominance of products with low benefit and insufficient investment in the development of technical and technological base. The proposed system of criteria and indicators can be significantly expanded depending on the ability of researchers to obtain additional information about the economic activities of forestry enterprises. Conclusions. A proposed method of assessing the level of economic security of forestry enterprises, which provides for determining the compliance of the current state of the business entity development goals (desired state), provides for the use of traditional indicators covering the main areas of economic activity of forestry enterprises. It is only important that the sample of forest enterprises is formed on the basis of belonging to the common forest area, similarity of forest area and forest area of these enterprises, as well as other factors that researchers may consider essential for the choice.